The MacroH2A1.1 – PARP1 Axis at the Intersection Between Stress Response and Metabolism - Hurtado-Bagès, Sarah; Guberovic, Iva; Buschbeck, Marcus (Frontiers in Genetics, 2018)
The exchange of replication-coupled canonical histones by histone variants endows chromatin with specific features. The replacement of the canonical H2A histone for the histone variant macroH2A is one of the most remarkable epigenetic modifications. The three vertebrate macroH2A proteins have a unique tripartite structure consisting of H2A-like domain, unstructured linker and macrodomain. Macrodomains are ancient globular folds that are able to bind NAD+ derived metabolites. Here, we will briefly describe the physiological relevance of the metabolite binding in the context of chromatin. In particular, we will focus on the macroH2A1.1 isoform that binds ADP-ribose and PARP1 enzyme, the cellular stress sensor. We will discuss the impact of this interaction in the context of cancer, senescence and cell energy metabolism.